Eksistensi Ritual Matani di Desa Manikliyu - Agus Darma Ariasa, I Wayan; Pujaastawa, Pujaastawa; Dharwiyantyo Putro, Bambang (Sunari Penjor : Journal of Anthropology, 2021)
Globalization already widespread in every regions of the world, it’s feared that the impact of globalization will have a negative influence on culture and one example of that culture is the matani ritual that’s owned by people of Manikliyu Village, Kintamani District, Bangli Regency, Bali. Formulation of problems in this study include 1) What’s form of matani ritual in Manikliyu Village? 2) What’s function of matani ritual fo Manikliyu’s people? 3) How’s  existence of the matani ritual in the globalization era? Generaly this research is focusing on existence of the matani ritual in Manikliyu Village as part of traditional culture in Bali Aga community. 2) Specifically from this study aims to explain, the form, function and existence of the ritual matani. The theories used in this research are, theory of Religion, Structural Functional theory, and  theory of globalization impact, because these theories can be basis of thinking in assessing the existence of matani rituals. Concepts used include: existence, influence of globalization and matani ritual. In this study, descriptive qualitative is the research method. With data sources called primary and secondary. The data collection techniques are observation, interviews, and literature study. The results found after conducting research are that ritual of matani still exists in midst of the globalization era, the people of Manikliyu Village have a special strategy in planting cultural values ??to next generation of villages so that culture possessed today especially matani rituals can survive and exist even in middle of  globalization era.